Potency and Agroforestry Patterns that Support Bamboo Sustainability in Sukaharja Village, Ciamis District - Aditya Hani; Eva Fauziyah; Tri Sulistyawati Widyaningsih; Devy Priambodo Kuswantoro (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2018)
Some people still thinks that bamboo has a low economic value. Many bamboo plants in the community are removed or replaced with other commodities. Sukaharja Village in Ciamis Regency is one of the centers that produce of bamboo. The community feels the economic benefits of the existence of the bamboo, so the existence of bamboo plants is still sustained. Bamboo management in Sukaharja Village can be used as a learning for bamboo farmers in other places. The study aims to determine the potential of agroforestry bamboo in Sukaharja Village. Potency of bamboo was collected by survey method. The observation plot was made as many as 39 plots. Vegetation observation and measurement was done by census (100 %) in all selected land area so that all types of compiler can be known. Parameters recorded/measured were bamboo species, number of clumps, number of tillers, number of young stems, number of old stems, stem height and stem circumference. Data related to socioeconomic obtained through interview. Respondents interviewed was chosen purposively by 69 respondents. Secondary data was obtained from literature study and data from agencies that are related to research objectives, such as District Forestry office, village office, and Agricultural Extension Agency, Fisheries, Livestock and Forestry. Bamboo in Sukaharja Village has a potential of 765 bamboo stems per hectare with 53 % composition of young bamboo and 47 % old bamboo, dominated by 92 % Gigantlochoa apus. Bamboo in Sukaharja village can be sustainable because it is cultivated with agroforestry pattern. The pattern of bamboo agroforestry in Sukaharja village community is a) Bamboo + wood, b) Bamboo + HHBK, c) Bamboo + plantation crop, d) Bamboo + horticulture.Keywords: agroforestry, bamboo, Sukaharja village, sustainability